Drug-Induced Urinary Stone of Atazanavir Incidentally Found in an Asymptomatic Patient: A Case Report - Maëlle Plawecki; Marie Bistoquet; Pierre-Edouard Grillet; Nicolas Abdo; Jean-Sébastien Souweine; Jean-Paul Cristol (Case Reports in Urology)
A HIV-infected female treated with a combination of emtricitabine/elvitegravir/tenofovir since 2017 presented an acute renal failure during her hospitalization for a SARS-CoV2 pneumonia. A computed tomography demonstrated left ureterohydronephrosis and ureteral stone. Fragments extracted by ureteroscopy showed a calculus composed of atazanavir and calcium oxalate. The patient’s medical history showed atazanavir intake during ten years and then discontinued in 2017. This case report emphasizes that drug-induced urolithiasis should be considered when renal function declines, even far from discontinuation of atazanavir and without clinical signs of renal colitis. Moreover, identification of risk factors should alert to the possibility of drug-induced nephrolithiasis.